Clinicopathological features, molecular mechanisms and prognosis of microcystic, elongated and fragmented (MELF) pattern in endometrial carcinoma: a review - Xiaobo Zhang; Yixuan Zhen (Gynecology and Obstetrics Clinical Medicine)
Endometrial carcinoma (EC) is one of the most common malignancies of the female reproductive system, with an increasing incidence and mortality rate. Endometrioid EC (EEC) was the most common type of EC. The microcystic, elongated and fragmented (MELF) pattern, a special mode of myometrial invasion newly discovered in recent years, mainly existed in low-grade EEC. Most EEC with MELF invasion had no specific molecular profile (NSMP EEC), and most NSMP EEC with MELF had a catenin beta 1 (CTNNB1) wild type. Apart from NSMP EEC, microsatellite instability-high was the most common molecular type. Initially considered a degenerative change, several researchers suggested an association between the MELF pattern and epithelial-mesenchymal transition. Several independent predictors of adverse outcomes, including tumour size, myometrial invasion, histological grade and lymphovascular space invasion, are related to the MELF pattern. This review aimed to remind pathologists of the clinicopathological features, molecular mechanisms and prognosis of the MELF pattern to avoid missed diagnosis or underdiagnosis.